A study of anemia and iron deficiency in chronic systolic heart failure - Kok Leng, Tan (2014)
Background: Iron deficiency (ID) is an emerging problem in patients with chronic systolic heart failure and can be a potential therapeutic target. However, not much is known about the frequency, predictors of iron deficiency and anemia in patients with chronic heart failure. Objectives: The primary objective of this study was to determine the frequency of iron deficiency in chronic systolic heart failure patients who were follow up in Hospital Universiti Sains Malaysia. The secondary objectives included were to determine the frequency of anemia in the same study population, correlation between ejection fraction and blood parameters and determining risk factors for anemia in chronic systolic heart failure. Methods: A total of 81 patients who were followed up in Hospital Universiti Sains Malaysia were recruited into this cross sectional study using purposive sampling method. These patients had history of chronic systolic heart failure for more than 6 months with left ventricular ejection fraction less than 45% as assessed by echocardiography using Simpson’s planimetric method. 10mls of venous blood was drawn from each participant and analyzed. Results: Thirty three patients were anemic (40.7%) as compared to 48 patients (59.3%) who did not. Sixteen patients were iron deficient (19.8%). All iron deficiency patients were anemic patients. There were positive correlation between serum ferritin (r=0.624, p<0.001), transferrin saturation (r= 0.346, p<0.001) and hemoglobin (r=0.528, p<0.001) with ejection fraction, respectively. Anemia in chronic systolic heart failure was independently associated with serum ferritin (OR 0.974, 95% CI 0.959, 0.988), transferrin saturation (OR 0.831, 95% CI 0.726, 0.952), and diabetes mellitus (OR 6.680, 95% CI 1.599, 27.897) based on multiple logistic regression analysis. Conclusion: This study demonstrated high frequency of anemia in chronic systolic heart failure patients. Majority of anemic patients were iron deficient. Besides that, serum hemoglobin and serum ferritin and transferrin saturation were positively correlated with left ventricular ejection fraction. It is recommended in future, an appropriately powered randomized trials with correction of anemia using erythropoietin and intravenous iron be carried out to validate the study findings.